The Specifics of the Russian Media Process in the Context of Transformations - Borisovich Simakov, Anastasiya Grigoryevna Vasilyeva, Natalya Rinatovna Balynskaya, Nina Vladimirovna Kuznetsova, Dmitry; Akulova, Irina Sergeevna (Opción, 2019)
The author examines the specifics of the Russian media process in the modern context and predicts its further development via the functional approach. As a result, despite the invariability of functions of stakeholders in the political process, there is still a manifestation of innovations in the mass media process with the involvement of all the members of modern society living under political laws. In conclusion, society, on the contrary, is increasingly using the political informer function, urging the media not only to accumulate opinions on pressing problems but also to produce them to the authorities in a consistent manner